2007
DOI: 10.1001/archneur.64.7.1015
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography Metabolic Correlates of Apathy in Alzheimer Disease

Abstract: Background: Apathy is the most common neuropsychiatric manifestation in Alzheimer disease (AD). Clinical, single-photon emission computed tomography, magnetic resonance imaging, and pathologic studies of apathy in AD have suggested an association with frontal dysfunction, most supportive of anterior cingulate abnormalities, but without a definitive localization. Objective: To examine the association between apathy and cortical metabolic rate on positron emission tomography in AD. Design: Forty-one subjects wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
134
2
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(151 citation statements)
references
References 24 publications
10
134
2
4
Order By: Relevance
“…lanctot and colleagues found similar results, showing decreased metabolism in left Acc and right oFc in Ad apathetic patients scanned with sPecT 60 . More recently, Marshall and colleagues, employing PeT in Ad patients with mild to moderate dementia, showed that apathy was related to hypometabolism in ventromedial PFc, including the ventral Acc and medial oFc 61 , as predicted and described below in our proposed account for neurobiology of apathy in Ad. PeT data from frontal variant of frontotemporal dementia (fvFTd) has also shown a significant relationship between apathy and oFc hypometabolism 62 .…”
Section: Apathy Alzheimer's Disease and Other Cortical Dementias: Nesupporting
confidence: 54%
“…lanctot and colleagues found similar results, showing decreased metabolism in left Acc and right oFc in Ad apathetic patients scanned with sPecT 60 . More recently, Marshall and colleagues, employing PeT in Ad patients with mild to moderate dementia, showed that apathy was related to hypometabolism in ventromedial PFc, including the ventral Acc and medial oFc 61 , as predicted and described below in our proposed account for neurobiology of apathy in Ad. PeT data from frontal variant of frontotemporal dementia (fvFTd) has also shown a significant relationship between apathy and oFc hypometabolism 62 .…”
Section: Apathy Alzheimer's Disease and Other Cortical Dementias: Nesupporting
confidence: 54%
“…1,2 Neuroimaging studies in neurodegenerative diseases have linked the state of cognitive inertia, characteristic of apathy, to decreased activity in a network that encompasses the dorsolateral prefrontal cortex, lateral aspects of the caudate nucleus and putamen, anterior cingulate cortex, and posterior parietal cortex. 33,[79][80][81][82] We have focused on Parkinson's disease as a model to study motivated behaviours, in which the symptoms of apathy are associated with defi cits in dopaminergic innervation from the mesolimbic and mesocortical pathways. Patients with Parkinson's disease who are exposed to non-physiological dopaminergic stimulation are at high risk of developing a range of behavioural addictions or impulse control disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In Alzheimer's disease, the degree of apathy severity has been linked to neurofi brillary tangles and volume loss in the medial prefrontal cortex, including the anterior cingulate cortex. 76 Accordingly, other functional imaging studies [79][80][81][82] have shown an association between apathy and hypometabolism in the medial orbitofrontal cortex and anterior cingulate cortex.…”
Section: Lesions and Neuroimagingmentioning
confidence: 99%
“…From a neuropathological point of view, dual-task-related gait changes in AD could reflect metabolic changes in cells of the associative cortices and hippocampal complex (Rolls and Grabenhorst 2008). The study of Marshall et al (2007) suggests that the reduction in glucose consumption and perfusion in the cingulate gyrus and orbitofrontal cortex may also explain the difficulty of patients with AD to perform dualtask walking.…”
Section: Prodromal Phase Of Parkinson's Diseasementioning
confidence: 99%